2010
DOI: 10.1093/hmg/ddq123
|View full text |Cite
|
Sign up to set email alerts
|

The FOXE1 locus is a major genetic determinant for radiation-related thyroid carcinoma in Chernobyl

Abstract: Papillary thyroid cancer (PTC) among individuals exposed to radioactive iodine in their childhood or adolescence is a major internationally recognized health consequence of the Chernobyl accident. To identify genetic determinants affecting individual susceptibility to radiation-related PTC, we conducted a genome-wide association study employing Belarusian patients with PTC aged 0-18 years at the time of accident and age-matched Belarusian control subjects. Two series of genome scans were performed using indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
127
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(135 citation statements)
references
References 26 publications
7
127
0
1
Order By: Relevance
“…It would therefore be interesting to study thyroid size and morphology in FOXE1-rs1443434 risk allele carriers using ultrasound. Various studies have identified the FOXE1 region as a susceptibility locus for thyroid cancer (33)(34)(35). A recent genome-wide association study identified a polymorphism (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It would therefore be interesting to study thyroid size and morphology in FOXE1-rs1443434 risk allele carriers using ultrasound. Various studies have identified the FOXE1 region as a susceptibility locus for thyroid cancer (33)(34)(35). A recent genome-wide association study identified a polymorphism (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The association between rs965513 and thyroid cancer risk has been independently confirmed in different populations (5)(6)(7)(8)(9)(10)(11). The association was also observed in familial PTC and in patients with radiation-induced PTC (12)(13)(14)(15). SNP rs965513 resides ∼60 kb upstream of forkhead box E1 (FOXE1) (also known as thyroid transcription factor 2), a critical transcription factor (TF) in thyroid development, differentiation, and function (16)(17)(18)(19).…”
mentioning
confidence: 87%
“…GWAS addressed the genetic predisposition to PTC and found two independent SNPs (rs944289 and rs965513) in the chromosomal regions containing nonannotated genes and a significant association with PTC (Gudmundsson et al 2009, 2012, Takahashi et al 2010. At 3.2-kb downstream of the SNP rs944289 in 14q.13.3, Albert de la Chapelle and his group identified a lincRNA gene and named it PTCSC3.…”
Section: Ptcsc3 (Papillary Thyroid Carcinoma Susceptibility Candidate 3)mentioning
confidence: 99%